Nickel-catalyzed C(sp(2))-H/C(sp(3))-H oxidative coupling of indoles with toluene derivatives - Soni, V.; Khake, S. M.; Punji, B. (ACS Catalysis, 2017)
Nickel-catalyzed oxidative C(sp(2))-H/C(sp(3))-H coupling of indoles with toluene derivatives is successfully achieved in the presence of 2-iodobutane as the oxidant. This method allows the selective C-2 benzylation of indoles with toluene derivatives over the alkylation with 2-iodobutane and permits the coupling of diversified indoles via the monochelation assistance. The reaction proceeded through a single-electron-transfer (SET) process, wherein both the C-H nickelation of indole and the C-H activation of toluene derivatives have a significant effect on the entire reaction rate. The synthetic utility of this nickel-catalyzed protocol is demonstrated by the facile removal of the directing group and by the convenient synthesis of the melatonin receptor antagonist Luzindole derivatives.